Religious Values in Clinical Practice are Here to Stay - Kørup, Alex Kappel (Journal of religion and health, 2020)
Research to date has shown that health professionals often practice according to personal values, including values based on faith, and that these values impact medicine in multiple ways. While some influence of personal values are inevitable, awareness of values is important so as to sustain beneficial practice without conflicting with the values of the patient. Detecting when own personal values, whether based on a theistic or atheistic worldview, are at work, is a daily challenge in clinical practice. Simultaneously ethical guidelines of tone-setting medical associations like American Medical Association, the British General Medical Council and Australian Medical Association have been updated to encompass physicians' right to practice medicine in accord with deeply held beliefs. Framed by this context, we discuss the concept of value-neutrality and value-based medical practice of physicians from both a cultural and ethical perspective, and reach the conclusion that the concept of a completely value-neutral physician, free from influence of personal values and filtering out value-laden information when talking to patients, is simply an unrealistic ideal in light of existing evidence. Still we have no reason to suspect that personal values, whether religious, spiritual, atheistic or agnostic, should hinder physicians from delivering professional and patient-centered care.